2021
DOI: 10.1096/fj.202101051r
|View full text |Cite
|
Sign up to set email alerts
|

Temporal relationship between alterations in the gut microbiome and the development of polycystic ovary syndrome‐like phenotypes in prenatally androgenized female mice

Abstract: It has been recently recognized that prenatal androgen exposure is involved in the development of polycystic ovary syndrome (PCOS) in adulthood. In addition, the gut microbiome in adult patients and rodents with PCOS differs from that of healthy individuals. Moreover, recent studies have suggested that the gut microbiome may play a causative role in the pathogenesis of PCOS. We wondered whether prenatal androgen exposure induces gut microbial dysbiosis early in life and is associated with the development of PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 59 publications
2
17
0
Order By: Relevance
“…We found that abnormalities appear in the gut microbiome as early as or even before PCOS‐like phenotypes manifest in PNA offspring 102 (Figure 4). Specifically, the reproductive phenotype of PCOS became apparent at puberty in the PNA offspring, which was followed by the appearance of the metabolic features of PCOS in young adulthood.…”
Section: Prenatal Exposure To Excess Androgens Alterations In the Gut...mentioning
confidence: 90%
See 2 more Smart Citations
“…We found that abnormalities appear in the gut microbiome as early as or even before PCOS‐like phenotypes manifest in PNA offspring 102 (Figure 4). Specifically, the reproductive phenotype of PCOS became apparent at puberty in the PNA offspring, which was followed by the appearance of the metabolic features of PCOS in young adulthood.…”
Section: Prenatal Exposure To Excess Androgens Alterations In the Gut...mentioning
confidence: 90%
“…We then studied the temporal relationship between the alterations in the gut microbiome and the development of PCOS‐like phenotypes. 102 The PCOS‐like reproductive phenotype was identified through the assessment of estrous cyclicity, ovarian histology, and serum testosterone concentration, and the metabolic phenotype was assessed using the measurement of body mass, the size of visceral adipocytes, insulin tolerance, and fasting blood glucose (FBG) concentration. We performed next‐generation sequencing (NGS) of fecal bacterial 16S rRNA genes to characterize the gut microbiomes of mice.…”
Section: Prenatal Exposure To Excess Androgens Alterations In the Gut...mentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the abundance of bacteria in PCOS with IR are different from PCOS-alone and healthy patients [69]. Moreover, some studies reported that prenatal androgen exposure may cause gut microbial dysbiosis and it may lead to PCOS in later life [70,71].…”
Section: Microbiota Dysbiosis Of Pcosmentioning
confidence: 99%
“…Previous studies have implicated that the alteration of gut microbiota may be involved in various diseases, including type 2 diabetes mellitus (T2DM), obesity, and nonalcoholic fatty liver disease (Canfora et al, 2019), and the incidence of these diseases also increased in PCOS (Azziz et al, 2016;Kumarendran et al, 2018;Zeng et al, 2021). Importantly, gut dysbacteriosis is found in clinical studies and animal research of PCOS (Lindheim et al, 2017;Liu et al, 2017;Kusamoto et al, 2021;Liang et al, 2021;Lin et al, 2021). Gut microbiota could be served as a key diagnostic biomarker in PCOS and cause insulin resistance (Yang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%